Ultra-high purity molybdenum dioxide dichloride, its loaded form and its preparation method
Patent Information
- Application Number
- JP2023574174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-01
- Filing Date
- 2022-05-20
- Publication Date
- 2025-04-11
AI Technical Summary
Existing methods for producing molybdenum dichloride dioxide (MoO2Cl2) fail to achieve ultra-high purity levels necessary for semiconductor applications due to high water and hydrogen chloride impurities, which contaminate deposition processes and degrade semiconductor performance.
A method involving heating low-purity molybdenum dichloride dioxide above its melting point to decompose hydrates and release hydrogen chloride, followed by filtration and venting to remove impurities, resulting in ultra-high purity MoO2Cl2 with residual impurity levels below ppm.
The process produces MoO2Cl2 with exceptionally low water and hydrogen chloride content, achieving bulk densities up to 3.0 g/cm³, suitable for semiconductor manufacturing with reduced contamination and improved film deposition quality.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The disclosed and claimed subject matter relates to ultra-high purity molybdenum dioxide dichloride (i.e., MoO2Cl2) that is substantially free of moisture (e.g., H2O), hydrogen chloride (HCl), and / or residual protons, loaded forms thereof, and methods for preparing same. [Background technology]
[0002] Thin films, particularly metal-containing thin films, have a variety of important applications, such as in nanotechnology and semiconductor device manufacturing. As a matter of fact, the semiconductor industry continues to advance with the deposition of continuous and conformal metal-containing thin films for advanced node applications. Examples of such applications include high refractive index optical coatings, corrosion protection coatings, photocatalytic self-cleaning glass coatings, biocompatible coatings, dielectric capacitor layers and gate electrode insulating films in field effect transistors (FETs), capacitor electrodes, gate electrodes, adhesive diffusion barriers, and integrated circuits. Additionally, metal and dielectric thin films are used in microelectronic applications, such as high-k dielectric oxides for dynamic random access memories (DRAMs), and non-ferroelectric perovskites used in infrared detectors and non-volatile random access memories (NV-FeRAMs).
[0003] Such techniques include reactive sputtering, ion-assisted deposition, sol-gel deposition, chemical vapor deposition (CVD) (also known as metalorganic CVD or MOCVD) and atomic layer deposition (also known as atomic layer epitaxy). CVD and atomic layer deposition (ALD) are used to produce conformal metal-containing films on substrates, such as silicon, silicon nitride, metal oxides and other metal-containing layers, using metal-containing precursors, and have the advantages of improved composition control, high film uniformity and effective control of doping.
[0004] In general, both CVD and ALD utilize the vapor of a volatile metal complex that is introduced into a process chamber where it contacts the surface of the wafer where a chemical reaction occurs to deposit a thin film of high purity metal or metal compound.
[0005] Conventional CVD is a chemical process in which precursors are used to form a thin film on a substrate surface. In a typical CVD process, precursors are passed over the surface of a substrate (e.g., a wafer) in a reaction chamber at low or ambient pressure. CVD occurs when the precursors react thermally at the wafer surface or react with co-added reagents in the process chamber, and film growth occurs in a steady-state deposition. In other words, the precursors react and / or decompose at the substrate surface to form a thin film of the deposited material. Volatile by-products are removed by gas flow through the reaction chamber. CVD can be applied in a continuous or pulsed mode to achieve a desired film thickness. However, in some applications, the thickness of the deposited film can be difficult to control because it depends on the joint action of many parameters, such as temperature, pressure, gas flow volume and uniformity, chemical depletion effects, and time.
[0006] ALD is also a method for the deposition of thin films. ALD is a self-limiting, continuous, and unique film growth technique based on surface reactions that can provide precise thickness control and can deposit conformal thin films of materials provided by precursors on surfaces of various compositions. In ALD, the precursors are separated during the reaction. A first precursor passes over the substrate surface and chemisorbs onto the chemical surface, forming a monolayer on the substrate surface. Any excess unreacted precursor is pumped out of the reaction chamber or purged (by an inert gas). A second precursor then passes over the substrate surface and reacts with the first precursor, forming a second monolayer of film on the substrate surface, on top of the first formed monolayer of film. This cycle can then be repeated multiple times to build up the metal or metal compound to the desired thickness with atomic precision. This is because the chemisorption of the precursors and reagents is self-limiting. ALD provides deposition of very thin, yet continuous, metal-containing films with precise control of film thickness, excellent film thickness uniformity, and remarkably conformal film growth to flatly coat deeply etched and highly complex structures, such as interconnect vias and trenches. However, for tight control of film thickness, it is important to avoid uncontrolled reactions with potential impurities that may be present in the precursors used in the deposition process. Trace impurities may affect film nucleation, film growth, film etching, and elemental steps of the deposition process.
[0007] For traditional chemical vapor deposition (CVD) processes, precursors and co-reactants are introduced into a deposition chamber via the gas phase to deposit a film of a certain thickness on a substrate. On the other hand, in atomic layer deposition (ALD) or ALD-like processes, precursors and co-reactants are introduced into the deposition chamber sequentially, thereby enabling surface-controlled layer-by-layer deposition and importantly self-limiting surface reactions to achieve atomic-level growth of thin films. The key for a good ALD deposition process is to invent a reaction scheme with precursors that consists of separation, self-limiting adsorption and reaction steps. One significant advantage of the ALD process is that it provides a much higher conformality with respect to the substrate, e.g., with an aspect ratio greater than 8, than CVD.
[0008] A variety of precursors may be used and a variety of deposition techniques may be employed to form metal-containing thin films. In this regard, molybdenum metal is a highly promising conductive metal for various applications in the semiconductor industry because it has low bulk resistivity, a short electron mean free path, and does not require a barrier between the dielectric and molybdenum layers.
[0009] Molybdenum dioxide dichloride has high vapor pressure, good thermal stability, and can be reduced by hydrogen to form molybdenum films, making it an attractive precursor for deposition of molybdenum-containing films by chemical vapor deposition or atomic layer deposition processes. See, for example, U.S. Patent Application Publication Nos. 2019 / 027573, 2019 / 067003, 2019 / 067014, 2019 / 067016, 2019 / 067094, and 2019 / 67095. CVD using molybdenum dioxide dichloride provides molybdenum metal films with low oxygen content, which is highly desired by the semiconductor industry. See KA Gesheva, K. Seshan, BO Seraphin, Thin Solid Films, 79, 39-49 (1981).
[0010] Due to its attractiveness for use in deposition processes, high purity molybdenum dioxide dichloride (MoO2Cl2) is desired for low resistivity molybdenum-containing films for interconnects, vias and contacts between first metal layers and silicon-based devices, and for wordline applications in DRAM and 3D NAND.
[0011] Molybdenum dioxide dichloride can be produced by several different routes. For example, MoO2Cl2 can be prepared by reacting MoO2 with elemental chlorine at 150-350°C. See R. Graham and L. Hepler, Journal of Physical Chemistry, 723 (1959). The crude product was purified by multiple sublimations. The authors report that different colored materials were obtained based on the purity of the material and the presence of water contaminants.
[0012] One other process proposed by Graham and Hepler involves the reaction of MoO3 with dry HCl, but this route gives only hydrated molybdenum dioxide dichloride (MoO2Cl2xH2O or MoO(OH)2Cl2). The authors report that the hydrate can be sublimed in the presence of excess HCl without decomposition.
[0013] One other process described in the aforementioned literature involves the reaction of MoO3 with NaCl to obtain MoO2Cl2 and Na2MoO4. See Zelikman et al., Zhurnal Obshchei Khimii, 24, 1916-20 (1954). However, this process requires relatively high temperatures (500°C) and produces significant amounts of solid by-products Na2MoO4 / Na2Mo2O7. In addition, the alkali metal halides contain residual moisture, which may contaminate the desired MoO2Cl2 during the solid condensation step.
[0014] A common problem with all known syntheses of MoO2Cl2 is their inability to provide MoO2Cl2 with sufficient purity for use in the electronics / semiconductor industry. In particular, MoO2Cl2 provided by known processes has high levels of hydrates (>1 wt%) as well as other impurities. For example, residual molybdenum dichloride dioxide hydrates (i.e., MoO2Cl2xH2O or H2MoO3Cl2) have a detrimental effect on the performance of the precursor in an ALD tool. The hydrates are relatively stable at room temperature and partially decompose at ampoule operating temperatures to form MoO3 and HCl. The formation of HCl gas during ampoule heating in an ALD tool causes a lower and unstable partial pressure of MoO2Cl2 during transport. Furthermore, the thermal decomposition of the hydrates may release moisture during heating, which causes highly corrosive "wet" HCl. The release of highly corrosive "wet" HCl may cause contamination of the precursor vapor with metal contaminants such as chlorides and oxychlorides of iron and chromium.
[0015] Metallic contaminants on the wafer surface are known to be a significant limiting factor to the yield and reliability of CMOS-based integrated circuits. Such contaminants degrade the performance of the ultra-thin SiO2 gate dielectrics that form the core of the individual transistors. Iron is one of the contaminants that cause the most difficulties in the IC industry. Iron is a very common element in nature and is difficult to eliminate in the manufacturing line. Iron contaminants have been found to significantly reduce the breakdown voltage of the gate oxide. The commonly reported mechanism for field breakdown defects from iron contaminants is the formation of iron precipitates at the SiO2 interface, which often penetrate the silicon dioxide. When dissolved in silicon, high levels of iron form act to degrade junction devices by carrier generation in the reverse bias depletion region. In bipolar junction transistors, the formation-recombination centers formed by dissolved iron generally increase the base current and reduce the emitter efficiency and base transport efficiency. See Istratov et al., Appl. Phys. A, 70, 489 (2000). Thus, precursors having extremely low levels of iron contamination are highly desirable. Purification methods for producing precursors such as MoO2Cl2 having extremely low levels of iron contamination are also desirable. Summary of the Invention [Problem to be solved by the invention]
[0016] As noted above, a need exists for ultra-high purity MoO2Cl2 that is free and / or substantially free of water and other proton-containing impurities for use in the electronics / semiconductor industries. [Means for solving the problem]
[0017] In one aspect, the disclosed and claimed subject matter relates to ultra-high purity MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0018] In one other aspect, the disclosed and claimed subject matter relates to a method for preparing ultra-high purity MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0019] In one other aspect, the disclosed and claimed subject matter relates to packed forms of ultra-pure MoO2Cl2 having high bulk density and high packing density, provided by packing a container containing ultra-pure MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0020] This summary section is not intended to identify every embodiment and / or incrementally novel aspect of the disclosed and claimed subject matter. Rather, this summary merely provides a preliminary discussion of different embodiments and corresponding points that are novel over the prior art and known art. For further details and / or a possible overall picture of the disclosed and claimed subject matter and embodiments, please refer to the Detailed Description section and corresponding figures of the present disclosure, further discussed below.
[0021] The order of discussion of the different steps described herein is provided for purposes of clarity. In general, the steps disclosed herein can be performed in any suitable order. Moreover, although each of the different features, techniques, configurations, etc. disclosed herein may be discussed in different parts of the disclosure, each of these concepts can be implemented independently of each other or in suitable combination with each other. Thus, the subject matter disclosed and claimed can be embodied and viewed in many different ways.
[0022] Detailed Description of the Drawings The accompanying drawings, which are included to provide a further understanding of the disclosed subject matter and are incorporated in and constitute a part of this specification, illustrate embodiments of the disclosed subject matter and, together with the specification, serve to explain the principles of the disclosed subject matter. [Brief description of the drawings]
[0023] [Figure 1] Figure 1H NMR spectra of crude MoO2Cl2 (a) containing 709 ppm water and ultra-pure MoO2Cl2 (b) containing 126 ppm H2O. The amount of water was determined based on the integration of the 1H NMR signals of protons in MoO2Cl2 and the internal standard. [Diagram 2] Shown are 1H NMR spectra of NMR solvent spiked with internal standard (a) and ultra-pure MoO2Cl2 (b) containing less than 20 ppm H2O. The blank subtraction method was used to determine the amount of water based on the integral of the protons in MoO2Cl2 and the protons in the internal standard. [Diagram 3] Dependence of the NMR signal of protons in MoO2Cl2 on the amount of water spiked in the NMR solvent (water blank). The chart shows the linear dependence of the NMR signal on the amount of water added to a solution of MoO2Cl2 in an NMR solvent. [Figure 4]IR spectra of vapor containing MoO2Cl2 and residual HCl are shown. The bottom spectrum shows the IR of vapor containing MoO2Cl2 at 190°C, where the absorbance of the HCl peak at 2799 cm-1 is 86.3 x 10-4 AU / meter at 0.5 cm-1 resolution. The middle spectrum shows the IR of vapor containing MoO2Cl2 at 190°C, where the absorbance of the HCl peak at 2799 cm-1 is 7.4 x 10-4 AU. The top spectrum shows the IR of vapor containing MoO2Cl2 at 150°C, where the absorbance of the HCl peak at 2799 cm-1 is 0.8 x 10-4 AU. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] definition Unless otherwise stated, the following terms used in the specification and claims have the following meanings for the present application.
[0025] For purposes of the disclosed and claimed subject matter, the numbering scheme for the periodic table groups follows the IUPAC Periodic Table of the Elements.
[0026] As used herein, the term "and / or" when used in phrases such as "A and / or B" is intended to include "A and B," "A or B," or "A" and "B."
[0027] The terms "substituents," "radicals," "groups," and "moieties" may be used interchangeably.
[0028] As used herein, the terms "metal-containing complex" (or simply "complex") and "precursor" are used interchangeably and refer to a metal-containing molecule or compound that can be used to prepare a metal-containing film by a vapor deposition process, such as by ALD or CVD. The metal-containing complex can be deposited on, adsorbed onto, decomposed at, transported to, and / or passed over a substrate or substrate surface to form a metal-containing film.
[0029] As used herein, the term "metal-containing film" includes not only elemental metal films, as more fully defined below, but also films that include a metal along with one or more elements, such as metal oxide films, metal nitride films, metal silicide films, metal carbide films, and the like. As used herein, the terms "elemental metal film" and "pure metal film" are used interchangeably and refer to a film that consists of or consists essentially of a pure metal. For example, an elemental metal film may include 100% pure metal, or an elemental metal film may include at least about 70%, at least about 80%, at least about 90%, at least about 95%, at least about 96%, at least about 97%, at least about 98%, at least about 99%, at least about 99.9%, or at least about 99.99% pure metal along with one or more impurities. Unless otherwise noted, the term "metal film" should be construed to mean an elemental metal film.
[0030] As used herein, the term "vapor deposition process" is used to refer to any type of vapor deposition technique, including, but not limited to, CVD and ALD. In various embodiments, CVD may be in the form of conventional (i.e., continuous flow) CVD, liquid injection CVD, or photo-assisted CVD. CVD may be in the form of a pulse technique, i.e., pulsed CVD. ALD is used to form a metal-containing film by vaporizing at least one metal complex disclosed herein and / or passing it over a substrate surface. For conventional ALD processes, see, for example, George SM et al., J. Phys. Chem., 1996, 100, 13121-13131. In other embodiments, ALD may be in the form of conventional (i.e., pulsed injection) ALD, liquid injection ALD, photo-assisted ALD, plasma-assisted ALD, or plasma-enhanced ALD. The term "vapor deposition process" further includes various vapor deposition techniques described in Chemical Vapour Deposition: Precursors, Processes, and Applications; Jones, AC; Hitchman, ML eds. The Royal Society of Chemistry: Cambridge, 2009; Chapter 1, pp. 1-36.
[0031] The terms "about" and "approximately," when used in reference to a measurable, numerical variable, refer to a specified value of the variable and all values of the variable that are within experimental error of the specified value (e.g., a 95% confidence limit on the mean), or within some percentage of the specified value (e.g., ±10%, ±5%), whichever is broader.
[0032] Preferably, the disclosed and claimed precursors are substantially free of proton source impurities. As used herein, the term "substantially free" when referring to proton source impurities is intended to mean any impurity that is substantially free of proton source impurities, as described in more detail below. 1By "absolutely zero" is meant the amount of such impurities resulting in less than about 30 ppm protons, individually or in the aggregate, from any of these impurities as determined by 1 H NMR.
[0033] Preferably, the disclosed and claimed precursors also contain metal ions or metals, such as Li + (Li), Na + (Na), K + (K), Mg 2+ (Mg), Ca 2+ (Ca), Al 3+ (Al), Fe 2+ (Fe), Fe 3+ (Fe), Ni 2+ (Fe), Cr 3+ The precursor is substantially free of Li, Na, K, Mg, Ca, Al, Fe, Ni, Cr, Ti, V, Mn, Co, Ni, Cu, or Zn. These metal ions or metals are potentially present from the starting materials / reactors used to synthesize the precursor. As used herein, the term "substantially free" means less than 5 ppm (by weight), preferably less than 3 ppm, more preferably less than 1 ppm, and most preferably less than 0.1 ppm, when referring to Li, Na, K, Mg, Ca, Al, Fe, Ni, Cr, Ti, V, Mn, Co, Ni, Cu, or Zn, as measured by ICP-MS.
[0034] Halo or halide refers to a halogen, F, Cl, Br, or I, linked to an organic moiety by one bond. In some embodiments, the halogen is F. In other embodiments, the halogen is Cl.
[0035] Halogenated alkyl is a fully or partially halogenated C1-C 20 It means alkyl.
[0036] Perfluoroalkyl refers to a linear, cyclic or branched saturated alkyl group as defined above in which all of the hydrogens have been replaced by fluorine (eg, trifluoromethyl, perfluoroethyl, perfluoropropyl, perfluorobutyl, perfluoroisopropyl, perfluorocyclohexyl, etc.).
[0037] MoO2Cl2 is substantially free of organic impurities resulting from either the starting materials used during synthesis or the by-products generated during synthesis. Examples include, but are not limited to, alkanes, alkenes, alkynes, dienes, ethers, esters, acetates, amines, ketones, amides, and aromatic compounds. As used herein, the term "free" of organic impurities means 1000 ppm or less as measured by GC, preferably 500 ppm or less (by weight) as measured by GC, and most preferably 100 ppm or less (by weight) as measured by GC or other analytical methods for assay. Importantly, the precursor, when used as a precursor for depositing ruthenium-containing films, preferably has a purity of 98 wt% or more, more preferably 99 wt% or more, as measured by GC.
[0038] Section headings used herein are for organizational purposes and are not to be construed as limiting the subject matter described. All documents or portions of documents cited in this application, including but not limited to patents, patent applications, articles, books, and treatises, are expressly incorporated herein by reference in their entirety for any purpose. In the event that any of the incorporated documents and similar materials defines a term in a manner that contradicts the term's definition in this application, this application controls.
[0039] Detailed Description It should be understood that both the foregoing general description and the following detailed description are exemplary and explanatory and are not intended to limit the claimed subject matter. The objects, features, advantages and ideas of the disclosed subject matter will be apparent to those skilled in the art from the description provided herein, and the disclosed subject matter can be readily implemented by those skilled in the art based on the description found herein. Any "preferred embodiment" and / or example descriptions illustrating preferred modes for implementing the disclosed subject matter are included for illustrative purposes and are not intended to limit the scope of the claims.
[0040] It will also be apparent to those skilled in the art that various modifications can be made in how the disclosed subject matter is implemented based on the embodiments described herein without departing from the spirit and scope of the subject matter disclosed herein.
[0041] As discussed above, the disclosed and claimed subject matter relates to ultra-high purity MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0042] In one other aspect, the disclosed and claimed subject matter relates to a method for preparing ultra-high purity MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0043] In one other aspect, the disclosed and claimed subject matter relates to packed forms of ultra-pure MoO2Cl2 having high bulk density and high packing density, provided by packing a container containing ultra-pure MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0044] The ultra-high purity MoO2Cl2 can be transferred to another vessel for bulk transport to a tool for deposition of molybdenum-containing films. In addition, ultra-high purity MoO2Cl2 exhibits substantially lower corrosion rates on steels (e.g., SS316) and alloys when used as a vapor.
[0045] Ultra-high purity MoO2Cl2, a method for its preparation and a container therefor are described below.
[0046] I. Ultra-pure MoO2Cl2 A. Impurities The disclosed and claimed subject matter includes ultra-pure MoO2Cl2 that is free or substantially free of residual H2O, HCl, other impurities and other proton sources undesirable for use of this precursor in depositing molybdenum-containing films. Further in this regard, the disclosed and claimed subject matter provides analytical methods for detecting small amounts of residual MoO2Cl2 hydrate, other proton source impurities in MoO2Cl2. Although the crystal structures of MoO2Cl2 and its hydrates are known (see, for example, LO Atovmyan, ZG A Liev, and BM Tarakanov, J. of Structural Chemistry, 9, 985-986 (1969); and Von FA Schroeder and AN Christensen, Z. Anorg. Allg. Chem., 392, 107-123 (1972)), the detection limits of X-ray powder diffraction analytical methods are not sufficient to detect low concentrations of MoO2Cl2 hydrate and other proton source impurities in MoO2Cl2. Thus, there is a need for more sensitive analytical methods to measure residual moisture, other impurities (e.g., MoO2Cl2 hydrate), and other proton source impurities (e.g., HCl) in MoO2Cl2.
[0047] Regardless of the detection method, the synthesis or availability of ultra-high purity MoO2Cl2 has not been reported, as, to date, such material has not been known or available in the art. As those skilled in the art will recognize, the primary source of proton impurities in MoO2Cl2 results from the reaction of MoO2Cl2 with water as follows: MoO2Cl2×H2O=MoO2Cl2+H2O MoO2Cl2×H2O=MoO3+2HCl Here, these reaction components have the following molecular weights (MW) and maximum relative amounts produced by decomposition of MoO2Cl2 hydrate: [Table 1]
[0048] Based on the above values, 1 The H NMR analysis allows the calculation of the maximum total proton source impurity level in ppm, where ppm means "parts per million by weight" (or "ppmw"), unless otherwise noted. [Table 2]
[0049] The disclosed and claimed subject matter provides ultra-high purity MoO2Cl2 with proton impurity levels on the order of less than 2 ppm, which represents approximately 100 times less purity than MoO2Cl2 provided by known "high purity" MoO2Cl2 and / or known processes for preparing MoO2Cl2.
[0050] 1. Total protons As described above, the ultra-high purity MoO2Cl2 of the disclosed and claimed subject matter can be prepared by physisorbing or chemisorbing MoO2Cl2, as described below. 1 It contains no, or substantially no, protons detectable by H NMR techniques, including protons derived from MoO2Cl2 hydrate, HCl, molybdic acid, and the like.
[0051] In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 50 ppm of protons in a physisorbed or chemisorbed state as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 40 ppm of protons in a physisorbed or chemisorbed state as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 30 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 25 ppm of protons in a physisorbed or chemisorbed state as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 20 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 15 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 10 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 9 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 8 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 7 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1It has less than about 6 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 5 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 4 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 3 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 2.5 ppm of protons in the physisorbed or chemisorbed state as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 2 ppm of physisorbed or chemisorbed protons as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 1.5 ppm of protons in the physisorbed or chemisorbed state as measured by H NMR. In one embodiment, the ultra-high purity MoO2Cl2 is 1 It has less than about 1 ppm of protons in a physisorbed or chemisorbed state as determined by 1 H NMR.
[0052] In one embodiment, the ultra-high purity MoO2Cl2 is 1 It contains no detectable protons as measured by H NMR. In one embodiment, 1 It contains no protons as determined by 1 H NMR.
[0053] 2. Moisture (H2O) As noted above, the ultra-high purity MoO2Cl2 of the disclosed and claimed subject matter is (as described herein) 1Contains no or substantially no residual HO as determined by H NMR.
[0054] In one embodiment, 1 The residual total HO content is less than about 250 ppm physisorbed or chemisorbed as measured by H NMR. 1 The residual total content of HO as measured by H NMR is less than about 200 ppm in the physisorbed or chemisorbed state. 1 The residual total HO content is less than about 150 ppm in a physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of HO as measured by H NMR is less than about 100 ppm in the physisorbed or chemisorbed state. 1 The residual total content of HO is less than about 75 ppm in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of HO as measured by H NMR is less than about 50 ppm in the physisorbed or chemisorbed state. 1 The residual total content of HO as measured by H NMR is less than about 25 ppm in the physisorbed or chemisorbed state. 1 The residual total content of HO is less than about 20 ppm in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of HO as measured by H NMR is less than about 15 ppm in the physisorbed or chemisorbed state. 1 The residual total content of HO as measured by H NMR is less than about 12.5 ppm in the physisorbed or chemisorbed state. In one embodiment, 1 The residual total content of HO as measured by H NMR is less than about 10 ppm in the physisorbed or chemisorbed state.
[0055] In one embodiment, 1 The residual total HO content, as measured by H NMR, is less than about 0.030 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.025 wt % in a physisorbed or chemisorbed state. In one embodiment, 1 The residual total HO content, as measured by H NMR, is less than about 0.020 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.015 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.014 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.013 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.012 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.011 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.010 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.009 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.008 wt % either physisorbed or chemisorbed. 1The residual total HO content, as measured by H NMR, is less than about 0.007 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.006 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.005 wt % in a physisorbed or chemisorbed state. In one embodiment, 1 The residual total HO content, as measured by H NMR, is less than about 0.004 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.003 wt % in a physisorbed or chemisorbed state. In one embodiment, 1 The residual total HO content, as measured by H NMR, is less than about 0.002 wt % either physisorbed or chemisorbed. 1 The residual total HO content, as measured by H NMR, is less than about 0.001 wt % in either a physisorbed or chemisorbed state.
[0056] In one embodiment, the ultra-high purity MoO2Cl2 is 1 It contains no detectable HO as measured by H NMR. In one embodiment, the ultra-pure MoOCl is 1 Contains no HO as determined by H NMR.
[0057] 3. Hydrochloric acid (HCl) A. HCl in physisorbed or chemisorbed states In one embodiment, the ultra-high purity MoO2Cl2 of the disclosed and claimed subject matter is (as described herein) 1 It is free or substantially free of residual HCl as determined by 1 H NMR.
[0058] In one embodiment, 1 The residual total HCl content is less than about 1000 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content is less than about 900 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content is less than about 800 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content is less than about 700 ppm physisorbed or chemisorbed as determined by H NMR. 1 The residual total HCl content is less than about 600 ppm physisorbed or chemisorbed as determined by H NMR. 1 The residual total HCl content is less than about 550 ppm physisorbed or chemisorbed as measured by H NMR. 1 The residual total HCl content is less than about 500 ppm physisorbed or chemisorbed as measured by H NMR. In one embodiment, 1 The residual total HCl content is less than about 450 ppm physisorbed or chemisorbed as determined by H NMR. 1 The residual total HCl content is less than about 400 ppm physisorbed or chemisorbed as determined by H NMR. 1 The residual total HCl content is less than about 350 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content is less than about 300 ppm physisorbed or chemisorbed as measured by H NMR. 1The residual total HCl content is less than about 250 ppm physisorbed or chemisorbed as measured by H NMR. 1 The residual total HCl content is less than about 200 ppm physisorbed or chemisorbed as measured by H NMR. In one embodiment, 1 The residual total HCl content is less than about 150 ppm physisorbed or chemisorbed as measured by H NMR. 1 The residual total HCl content is less than about 125 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content is less than about 90 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content is less than about 80 ppm physisorbed or chemisorbed as determined by H NMR. 1 The residual total HCl content is less than about 70 ppm physisorbed or chemisorbed as measured by H NMR. 1 The residual total HCl content is less than about 60 ppm physisorbed or chemisorbed as measured by H NMR. 1 The residual total HCl content is less than about 50 ppm physisorbed or chemisorbed as determined by H NMR. In one embodiment, 1 The residual total HCl content, as measured by 1 H NMR, is less than about 40 ppm in the physisorbed or chemisorbed state.
[0059] In one embodiment, the ultra-high purity MoO2Cl2 is 1 It contains no detectable HCl as determined by H NMR. In one embodiment, the ultra-pure MoO2Cl2 is 1 Contains no HCl as determined by H NMR.
[0060] B. HCl in the gas phase In one embodiment, the ultra-high purity MoO2Cl2 of the disclosed and claimed subject matter contains no or substantially no residual HCl as measured by infrared spectroscopy (IR) or tunable diode laser absorption spectroscopy (TDLAS). In one embodiment, for example, the ultra-high purity MoO2Cl2 gas phase contains no HCl as measured by Fourier transform infrared spectroscopy (FT-IR).
[0061] In one embodiment, the ultra-high purity MoO2Cl2 gas phase produced from the ultra-high purity solid MoO2Cl2 prepared according to the disclosed and claimed subject matter exhibits a peak at 2600-3100 cm3 due to gaseous HCl. -1 In one embodiment, the HCl-containing sol is free of detectable HCl as measured by the FT-IR peak at 2799 cm -1 The HCl peak at is used to quantify the amount of HCl in the MoO2Cl2 gas phase.
[0062] In one embodiment, the MoO2Cl2 gas phase has a peak at 2799 cm -1 The absorbance of the HCl peak is 0.5 cm -1 with a resolution of 100×10 -4 In one embodiment, the absorbance at 2799 cm in the gas phase of MoOCl is less than 1. -1 The absorbance of the HCl peak is 0.5 cm -1 with a resolution of 50×10 -4 In one embodiment, the absorbance at 2799 cm in the gas phase of MoOCl is less than 1. -1 The absorbance of the HCl peak is 0.5 cm -1 with a resolution of 10 x 10 -4 In one embodiment, the absorbance at 2799 cm in the gas phase of MoOCl is less than 1. -1 The absorbance of the HCl peak is 0.5 cm -1 with a resolution of 5×10 -4 In one embodiment, the absorbance at 2799 cm in the gas phase of MoOCl is less than 1.-1 The absorbance of the HCl peak is 0.5 cm -1 with a resolution of 1×10 -4 Less than absorbance units / meter.
[0063] In one embodiment, the ultra-pure MoO2Cl2 contains no detectable HCl as measured by IR. In one embodiment, the ultra-pure MoO2Cl2 contains no HCl as measured by IR.
[0064] In one embodiment, the disclosed and claimed subject matter comprises a gas phase (i.e., gas) comprising, consisting essentially of, or consisting of MoO2Cl2, the gas phase being free or substantially free of gaseous HCl. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 300 ppm volume as measured by IR. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 150 ppm volume as measured by IR. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 100 ppm volume as measured by IR. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 60 ppm volume as measured by IR. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 30 ppm volume as measured by IR. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 15 ppm by volume as measured by IR. In one embodiment, the concentration of gaseous HCl in the MoO2Cl2 gas phase is less than 3 ppm by volume as measured by IR.
[0065] 4. MoO2Cl2 hydrate As noted above, the ultra-high purity MoO2Cl2 of the disclosed and claimed subject matter is obtained by subjecting the MoO2Cl2 to a process (described herein) 1It is free or substantially free of residual MoO2Cl2 hydrate as determined by H NMR. The chemical formulas MoO2Cl2×H2O, MoO(OH)2Cl2, and H2MoO3Cl3 are commonly used to describe the hydrates.
[0066] In one embodiment, 1 The residual total content of MoO2Cl2×H2O is less than about 0.30 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.25 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.20 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.15 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.14 wt % in a physisorbed or chemisorbed state as determined by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.13 wt % in a physisorbed or chemisorbed state as determined by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.12 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.11 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.10 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1The residual total content of MoO2Cl2×H2O is less than about 0.09 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.08 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.07 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.06 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.05 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.04 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.03 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.02 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O is less than about 0.015 wt % in the physisorbed or chemisorbed state as measured by H NMR. 1 The residual total content of MoO2Cl2×H2O, as measured by H NMR, is less than about 0.01 wt % in the physisorbed or chemisorbed state.
[0067] In one embodiment, the ultra-high purity MoO2Cl2 is 1Contains no detectable MoO2Cl2×H2O as measured by H NMR. In one embodiment, ultra-pure MoO2Cl2 is 1 Contains no MoO2Cl2×H2O as determined by H NMR.
[0068] 4. MoO3 As stated above, the MoO2Cl2 of the disclosed and claimed subject matter does not contain or is substantially free of residual MoO3. In one embodiment, the residual total content of MoO3 is less than about 0.20 wt% in the physisorbed or chemisorbed state. In one embodiment, the residual total content of MoO3 is less than about 0.15 wt% in the physisorbed or chemisorbed state. In one embodiment, the residual total content of MoO3 is less than about 0.14 wt% in the physisorbed or chemisorbed state. In one embodiment, the residual total content of MoO3 is less than about 0.13 wt% in the physisorbed or chemisorbed state. In one embodiment, the residual total content of MoO3 is less than about 0.12 wt% in the physisorbed or chemisorbed state. In one embodiment, the residual total content of MoO3 is less than about 0.11 wt% in the physisorbed or chemisorbed state. In one embodiment, the residual total content of MoO3 is less than about 0.10 wt% in a physisorbed or chemisorbed state.
[0069] B. Bulk Density As noted above, the ultra-pure MoO2Cl2 of the disclosed and claimed subject matter has a purity of 3.0 g / cm 3 The bulk density of MoO2Cl2 is defined by the mass of MoO2Cl2 per volume occupied by the sample, g / cm 3 Typically, MoO2Cl2 has a density of 1 g / cm 3 The bulk density of MoO2Cl2 is produced in powder or crystalline form with low bulk density and high surface area less than 100 nm. For example, the bulk density of the disclosed and claimed MoO2Cl2 is less than the previously reported bulk density values for MoO2Cl2 described in WO2020 / 021786 (0.8-1.2 g / cm3).3 ) is twice as high.
[0070] In one embodiment, the ultra-pure MoO2Cl2 has a concentration of about 2.0 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.1 g / cm 3 In one embodiment, ultrapure MoO2Cl2 has a bulk density of about 2.2 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.3 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.4 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.5 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.6 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.7 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.8 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 2.9 g / cm 3 In one embodiment, ultra-pure MoO2Cl2 has a bulk density of about 3.0 g / cm 3 It has a bulk density of .
[0071] II. Method for preparing ultra-high purity MoO2Cl2 As stated above, the disclosed and claimed subject matter relates to a method for preparing ultra-high purity MoO2Cl2 by heating low purity molybdenum dichloride dioxide (e.g., comprising hydrated molybdenum dichloride, H2MoO3Cl2) above its melting point in a sealed container. In one aspect of this embodiment, the headspace of the container is vented at least once to remove hydrogen chloride and other by-products present in the crude molybdenum dichloride dioxide.
[0072] Without wishing to be bound by theory, heating low purity MoO2Cl2 above its melting point results in the decomposition of MoO2Cl2 hydrates and other impurities (e.g. hydrogen chloride and water molecules). This is believed not to occur in processes where MoO2Cl2 is not treated above its melting point. During the dissolution process, the molybdenum trioxide by-product settles to the bottom of the vessel, allowing for better separation from the hydrogen chloride by-product. Notably, this approach contrasts with known procedures for purifying these types of precursors. For example, WO 2019 / 115361 describes a method for purifying various precursors at temperatures below their melting points. However, unexpectedly, it has been found that performing a melting step is very effective and important for removing residual traces of H2O and HCl trapped in the solid in order to achieve ultra-high purity MoO2Cl2 with a purity level that was previously unobtainable. Indeed, a further advantage of the disclosed and claimed process is that the molten MoO2Cl2 can be filtered to remove insoluble impurities such as MoO3 and MoO2.
[0073] As noted above, in one embodiment, the disclosed and claimed process for preparing ultra-high purity MnO2Cl2 comprises: a. charging low purity MoO2Cl2 into a pressure vessel; b. heating the container to a temperature sufficient to melt the low-purity MoO2Cl2 (approximately, about 180°C to about 200°C); c. optionally filtering the molten MoO2Cl2 to remove insoluble impurities (e.g., MoO3 and MoO2); d. venting the vessel to remove impurities (e.g., HCl gas); e. cooling the container; f. Optionally, re-venting the vessel. Includes. In one aspect of this embodiment, steps a-f are repeated until the vessel is filled. In one aspect of this embodiment, one or more of steps a-f are repeated until the vessel is filled. In one aspect of this embodiment, the vessel is constructed of a non-corrosive material, such as stainless steel, nickel, Monel, Hastelloy, nickel-coated stainless steel, etc. In another aspect of this embodiment, the vessel is equipped with at least one valve and is connected to a metal system equipped with a pressure gauge and a second valve.
[0074] In one embodiment, low purity MoO2Cl2 powder is loaded into a pressure vessel. The vessel with MoO2Cl2 is heated to about 180°C to about 200°C to completely melt the low purity MoO2Cl2. The vessel is cooled to ambient temperature and the headspace of the vessel is evacuated or purged with an inert gas to remove residual hydrogen chloride gas and other possible impurities present in the gas phase. In one aspect of this embodiment, the vessel is constructed of a non-corrosive material, such as stainless steel, nickel, Monel, Hastelloy, nickel-coated stainless steel, etc. In one other aspect of this embodiment, the vessel is equipped with at least one valve and is connected to a metal system equipped with a pressure gauge and a second valve.
[0075] In one other embodiment, the low purity MoO2Cl2 powder is loaded into a pressure vessel equipped with at least one valve and connected to a metal system equipped with a pressure gauge and a second valve. The vessel with low purity MoO2Cl2 is heated to about 180°C to about 200°C to completely melt the MoO2Cl2 powder. At this temperature, the head space of the vessel is vented to a second vessel (containing an inert gas) at a lower pressure compared to the vessel with MoO2Cl2. This process may be repeated until the pressure of the MoO2Cl2 vessel is within 20% of the pressure of the MoO2Cl2 gas phase expected at the vessel temperature. In one aspect of this embodiment, the vessel is constructed of a non-corrosive material, such as stainless steel, nickel, Monel, Hastelloy, nickel-coated stainless steel, etc. Note that in this embodiment, the vessel with low purity MoO2Cl2 may alternatively be vented or evacuated at a lower temperature.
[0076] As mentioned above, the method may include a step of filtering the molten MoO2Cl2 to remove insoluble solids in the melt. Filtering the melt allows for the removal of decomposition by-products and impurities, if any, formed during heating, which are not possible when the precursor is processed at temperatures below the melting point.
[0077] III. Packed forms of ultra-pure MoO2Cl2 As stated above, the disclosed and claimed subject matter relates to packed forms of ultra-pure MoO2Cl2 having high bulk density and high packing density. Such forms are provided by filling containers containing ultra-pure MoO2Cl2 that is free and / or substantially free (ppm level or lower) of water and other impurities for use in the electronics / semiconductor industry.
[0078] Handling low bulk density powders with large surface areas can be a source of moisture contaminants. Furthermore, filling low bulk density powders with large surface areas into containers designed for semiconductor manufacturing can cause scattering and contamination of container parts by the powder. Furthermore, in the semiconductor industry, fabrication facility (fab) floor space is expensive, so it is desirable to provide precursor materials in containers with minimal space / footprint requirements. Therefore, containers with small footprints and high packing densities are preferred for chemical transport cabinets.
[0079] In this regard, WO 2020 / 021786 describes a process for producing MoO2Cl2, which involves subliming and re-agglomerating crude molybdenum oxychloride in a reducing atmosphere. However, the MoO2Cl2 produced by this process has a relatively low bulk density (e.g., 1.2 g / cm3). 3 Although precursor vaporization equipment is known (see, for example, U.S. Patent Application Publication No. 2019 / 0186003, which provides a vaporizer for vaporization and transport of the vapor phase to a deposition tool), such equipment contains multiple trays and is not suitable for filling the vaporizer with molten solids to achieve optimal (i.e., the highest possible) packing density.
[0080] As noted above, the ultra-pure MoO2Cl2 of the disclosed and claimed subject matter has a purity of 3.0 g / cm 3 The results show that the bulk density of MoO2Cl2 is unexpectedly high, ranging from 100 to 1000 MPa. Thus, ultra-high purity MoO2Cl2 can be provided in packed form (e.g., in a canister container where the pressure does not exceed the sum of the partial pressure of the molybdenum dioxide dichloride and the partial pressure of the inert gas used to fill the headspace of the canister). As explained above, the bulk density of MoO2Cl2 is defined as the mass of the MoO2Cl2 sample divided by the volume occupied by the sample and is expressed in g / cm 3The packing density of a packed form of ultrapure MoO2Cl2 is defined as the percentage of the total external volume of the packed form containing ultrapure MoO2Cl2, excluding the valve manifold, and is expressed in kg / liter of MoO2Cl2 (external volume). Given the unexpectedly high bulk density of ultrapure MoO2Cl2, the packed form has an equally unexpected packing density.
[0081] In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 0.7 kg / L to about 1.5 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 0.7 kg / L to about 1.0 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.0 kg / L to about 1.5 kg / L (external container volume).
[0082] In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 0.7 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 0.8 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 0.9 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.0 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.1 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.2 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.3 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.4 kg / L (external container volume). In one embodiment, the packed form of ultra-high purity MoO2Cl2 has a packing density of about 1.5 kg / L (external container volume).
[0083] In one embodiment, the packed form of ultra-pure MoO2Cl2 is provided in a container similar to the shape of a gas cylinder. In one aspect of this embodiment, the container has a height / diameter ratio of at least 2 / 1. In one aspect of this embodiment, the container has a height / diameter ratio of at least 3 / 1. In one aspect of this embodiment, the container has a height / diameter ratio of at least 4 / 1. In one aspect of this embodiment, the container has a height / diameter ratio of at least 5 / 1. In a further aspect of this embodiment, the container comprises (or may comprise) at least one valve and an inlet tube for filling with molten ultra-pure MoO2Cl2, the inlet tube belonging to the head space above the filled material. EXAMPLES
[0084] example Reference is now made to more specific embodiments of the disclosure and experimental results that provide support for such embodiments. Examples are provided below to more fully illustrate the disclosed aspects and should not be construed as limiting the disclosed subject matter in any way.
[0085] It will be apparent to those skilled in the art that various modifications and variations can be made in the disclosed subject matter and the specific examples provided herein without departing from the spirit or scope of the disclosed subject matter. Thus, the disclosed subject matter, including the description provided by the following examples, is intended to cover modifications and variations of the disclosed subject matter that come within the scope of any claims and their equivalents.
[0086] method 1 H NMR analysis Proton NMR is used as an analytical method to detect low levels (i.e., 0.1 wt% or less) of moisture and residual hydrogen atoms in ultrapure MoO2Cl2. In this method, the moisture and total proton content in ultrapure MoO2Cl2 samples was measured by integration of the water peak of a 5 wt% solution of ultrapure MoO2Cl2 in CD3CN using ethylene carbonate as an internal standard and blank subtraction.
[0087] A 5 mm Wilmad low pressure / vacuum NMR tube was filled with ethylene carbonate (0.008 g) and CDCN (1.000 g) under a N2 atmosphere. 512 scans, 1 second relaxation time were used on a Bruker Ascend 500 MHz NMR. 1 A H NMR spectrum was collected. MoO2Cl2 (0.050 g) was then dissolved in the solution under N2 atmosphere. 1 1 H NMR spectra were collected.
[0088] Using MestReNova software, the peak at 4.45 ppm corresponding to the -CH2- group in ethylene carbonate and the peak at 2.13 ppm corresponding to H2O in the blank were integrated. In the MoO2Cl2 sample, the internal standard at 4.45 ppm and the broad ultrapure MoO2Cl2·×H2O peak at 5.24 ppm were integrated and blank subtraction was used to determine the water content in ultrapure MoO2Cl2. The method detection limit for this method was estimated to be 10 ppm H2O in ultrapure MoO2Cl2, which is equivalent to 1.1 ppm total protons in MoO2Cl2.
[0089] This analysis was used for all MoO2Cl2 samples prepared according to the disclosed and claimed subject matter processed.
[0090] Example 1: Preparation of ultra-high purity MoO2Cl2 A low-purity MoO2Cl2 sample with low bulk density and high water content was prepared using the above 1 The sample was analyzed by H NMR method. The water content in the sample was 709 ppm (equivalent to a total residual proton content of 78.8 ppm in low-purity MoO2Cl2) and the bulk density was 0.3 g / cm 3 The low purity MoO2Cl2 (5.7 kg) was charged into a 21 L C-22 Hastelloy vessel and heated to 200 °C to completely dissolve the MoO2Cl2. The vessel was heated at 200 °C for 24 hours to decompose the residual hydrates and release hydrogen chloride. The vessel was then cooled to room temperature and the residual gases were removed under a nitrogen purge. An additional 5.0 kg of low purity MoO2Cl2 was then charged on top of the solidified MoO2Cl2 melt in the 21 L C-22 Hastelloy vessel and heated to 200 °C to completely melt the low purity MoO2Cl2. The vessel was heated at 200 °C for 24 hours to decompose the residual hydrates and release hydrogen chloride. The above process was repeated two more times to fill the 21 L container with 20.6 kg of ultra-high purity MoO2Cl2.
[0091] analysis: The bulk density of ultrapure MoO2Cl2 was determined by measuring the void volume of the container to be 2.6 g / cm 3 A representative sample from the container was 1 Analysis by H NMR showed a residual moisture content of 126 ppm in ultrapure MoO2Cl2 (equivalent to a total residual proton content of 14 ppm in ultrapure MoO2Cl2).
[0092] Example 2: Bulk density of ultra-pure MoO2Cl2 Low density MoO2Cl2 powder (4.2 g) was loaded into an SS316 tube with an internal diameter (ID) of 10 mm. The tube with low purity MoO2Cl2 powder was capped with an SS316 VCR cap and heated at 185 °C for 22 h. The tube was cooled to room temperature and residual gas was removed by nitrogen purging. The ultra-pure MoO2Cl2 formed a solid block at the bottom of the container with a diameter of 10 mm and a height of 19 mm. The bulk density of the ultra-pure MoO2Cl2 was 2.8 g / cm 3 In comparison, the bulk density of the low-purity MoO2Cl2 described in WO 2020 / 021786 is about 0.8-1.2 g / cm 3 It has been reported that.
[0093] Example 3: Container / vaporizer with high packing density MoO2Cl2 A container with 20 kg of low purity MoO2Cl2 prepared as shown in Example 1 was heated at 200°C to completely dissolve the low purity MoO2Cl2. The molten liquid was transferred to a container / vaporizer with an external diameter of 9.2 inches and a height of 51 inches (aspect ratio of 5.5) equipped with a valve and an inlet tube. The transfer was repeated at least once to fill the 44 L container with 40 kg of MoO2Cl2. During cooling, the container / vaporizer was vented to release excess pressure due to hydrogen chloride formed by decomposition of proton-containing species initially present in the low purity MoO2Cl2 powder. Samples of ultra-high purity MoO2Cl2 from the container / vaporizer were collected by vaporizing MoO2Cl2 at 160°C-180°C and condensing it on a cold surface. The above-mentioned 1 The sample was analyzed by H NMR and the residual water content in ultra-pure MoO2Cl2 was less than about 20 ppm (equivalent to less than about 2.2 ppm total residual protons in ultra-pure MoO2Cl2).
[0094] Example 4: Preparation of ultra-high purity MoO2Cl2 A low-purity MoO2Cl2 sample with low bulk density and high water content was prepared as described above. 1 The sample was analyzed by H NMR method. The water content in the sample was 1074 ppm (equivalent to 119.4 ppm total residual protons in low-purity MoO2Cl2) and the bulk density was 0.3 g / cm 3 The low purity MoO2Cl2 (6.4 kg) was charged into a 21 L C-22 Hastelloy vessel and heated to 200°C to completely dissolve the MoO2Cl2. The vessel was heated at 200°C for 12 hours to decompose the residual hydrates and release hydrogen chloride. The vessel was then cooled to room temperature and the residual gases were removed under a nitrogen purge. An additional 4.0 kg of low purity MoO2Cl2 was then charged on top of the solidified MoO2Cl2 melt in the 21 L C-22 Hastelloy vessel and heated to 200°C to completely dissolve the low purity MoO2Cl2. The vessel was heated at 200°C for 12 hours to decompose the residual hydrates and release hydrogen chloride. After cooling, the 21 L container contained 10.4 kg of ultra-high purity MoO2Cl2.
[0095] analysis The bulk density of ultrapure MoO2Cl2 is 3.0 g / cm3 as determined by measuring the void volume of the container. 3 A representative sample from the container was 1 Analysis by H NMR showed less than 15 ppm residual moisture in ultra-pure MoO2Cl2 (equivalent to less than 2 ppm total residual protons in ultra-pure MoO2Cl2).
[0096] Example 5: Bulk density of ultra-pure MoO2Cl2 The low purity MoO2Cl2 powder (10.4 kg) was loaded into a 21 L C-22 Hastelloy vessel and heated to 200 °C to completely dissolve the MoO2Cl2. Then, while at 200 °C, 9.8 kg of liquid MoO2Cl2 was transferred into an 8.8 L C-22 Hastelloy vessel. The 8.8 L vessel was gradually cooled to room temperature by first cooling the bottom for 4 hours and then cooling the top of the vessel until the vessel was at ambient temperature. At ambient temperature, residual gas was removed by vacuum. The ultrapure MoO2Cl2 formed a solid block at the bottom of the vessel with a diameter of 222 mm and a height of 85.6 mm. The bulk density of the ultrapure MoO2Cl2 is 2.96 g / cm 3 For comparison, the bulk density of low-purity MoO2Cl2 described in WO 2020 / 021786 is about 0.8-1.2 g / cm 3 It has been reported that.
[0097] Comparative Example 6: MoO2Cl2 collected from low purity MoO2Cl2 In this comparative example, MoO2Cl2 was not purified or packaged by the disclosed method. A container containing 5.7 kg of impure MoO2Cl2 with a moisture level of 390 ppm (equivalent to 43.4 ppm total residual protons in impure MoO2Cl2) was prepared as in Example 1 and heated to 150°C, below the melting point of MoO2Cl2. A small amount of the hot solid was vapor-transferred to an evacuated container with ambient internal surface temperature for 30 seconds. The impure MoO2Cl2 at 150°C was allowed to re-equilibrate for 1.5 hours. A 30 second vapor transfer was performed to the same evacuated container. This 30 second transfer with 1.5 hour re-equilibration was repeated four more times for a total of six hot vapor transfers. All containers were cooled to ambient temperature. The 135 g of material collected in the evacuated receiving vessel had a moisture level of 373 ppm (equivalent to less than about 41.5 ppm total residual protons in ultra-high purity MoO2Cl2). This example showed that MoO2Cl2 collected from low purity material contained a significant amount of moisture (373 ppm) compared to MoO2Cl2 collected from ultra-high purity MoO2Cl2 (less than 20 ppm).
[0098] Example 7: Measurement of HCl concentration in MoO2Cl2 gas phase A Hastelloy C22 vessel was filled with MoO2Cl2. The vessel was connected to a Hastelloy pneumatic valve and a SS vacuum manifold. The vessel with MoO2Cl2 was heated to 190°C to melt the MoO2Cl2 and release traces of residual HCl into the gas phase. The residual HCl was purged from the headspace above the MoO2Cl2 with purified N2 to obtain ultra-pure MoO2Cl2. During the purge, the N2 carrier gas containing the MoO2Cl2 gas phase was flowed through a 5.33 meter IR cell of an FT-IR spectrometer (MKS Multigas 2030) heated to 150°C. The 2799 cm -1 The absorbance of the HCl peak is 0.5 cm -1 with a resolution of 0.0088 to at least 7.4 x 10 -4The absorbance units per meter of HCl was reduced to 1000 s. Figure 4 shows the IR spectrum of the gas phase containing MoO2Cl2 and residual HCl, and shows the 2799 cm -1 The absorbance of the HCl peak is 86.3 x 10 -4 and 7.4 x 10 -4 After purging was completed, the vessel with ultra-pure MoO2Cl2 was cooled to 135°C and the MoO2Cl2 gas phase was continuously flowed through the 5.33 meter IR cell of the FT-IR spectrometer. -1 The absorbance of the HCl peak is 0.8 x 10 -4 The calculated concentration of HCl in the gas phase was 3.4 ppm. As mentioned above, Figure 4 shows the 2799 cm -1 The absorbance of the HCl peak is about 0.8 x 10 -4 This indicates that it is AU / meter.
[0099] summary It has been shown that ultra-pure MoO2Cl2 can be prepared at purity levels nearly 100 times higher than previously reported, and that this high-purity MoO2Cl2 has the unexpected property of providing its extremely densely packed morphology.
[0100] Although the disclosed and claimed subject matter has been described and illustrated with a certain degree of particularity, it is to be understood that the disclosure is for purposes of illustration only and that many variations in the conditions and sequence of steps may occur to those skilled in the art without departing from the spirit and scope of the disclosed and claimed subject matter.
Claims
1. 1 Ultra-pure MoO with less than 30 ppm of protons in the physisorbed or chemisorbed state as measured by H NMR. 2 C 2 .
2. 1 10. The ultra-high purity MoO of claim 1, having less than 15 ppm of protons in the physisorbed or chemisorbed state as measured by H NMR. 2 C 2 .
3. 1 10. The ultra-high purity MoO of claim 1, having less than 3 ppm of protons in the physisorbed or chemisorbed state as measured by H NMR. 2 C 2 .
4. 1 Less than 250 ppm H physisorbed or chemisorbed as measured by H NMR. 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
5. 1 Less than 125 ppm H physisorbed or chemisorbed as measured by H NMR. 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
6. 1 Less than 50 ppm H physisorbed or chemisorbed as measured by H NMR. 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
7. 1 Less than 15 ppm H physisorbed or chemisorbed as measured by H NMR. 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
8. 1 Less than 0.005 wt. % H physisorbed or chemisorbed as measured by H NMR. 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
9. 1 10. The ultra-high purity MoO of claim 1, having a residual total content of HCl in the physisorbed or chemisorbed state of less than 1000 ppm as measured by H NMR. 2 C 2 .
10. 1 Less than 0.30 wt % MoO physisorbed or chemisorbed as measured by H NMR. 2 C 2 ×H 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
11. 1 Less than 0.10 wt % MoO physisorbed or chemisorbed as measured by H NMR. 2 C 2 ×H 2 2. The ultra-high purity MoO of claim 1 having a residual total content of O. 2 C 2 .
12. Less than 0.20 wt% of MoO in a physisorbed or chemisorbed state. 3 The ultra-high purity MoO of claim 1 having a residual total content of 2 C 2 .
13. 2.0g / cm 3 The ultra-high purity MoO of any one of claims 1 to 12, having a bulk density of 2 C 2 .
14. 2.5g / cm 3 The ultra-high purity MoO of any one of claims 1 to 12, having a bulk density of 2 C 2 .
15. 3.0g / cm 3 The ultra-high purity MoO of any one of claims 1 to 12, having a bulk density of 2 C 2 .
16. a. Low-purity MoO 2 C 2 charging the mixture into a pressure vessel; b. The low-purity MoO 2 C 2 heating the container to a temperature sufficient to melt d. venting the vessel to remove impurities; and e. cooling the container; The ultra-high purity MoO of claim 1, 2 C 2 Method for preparing the compound.
17. The method of claim 16, further comprising the step of filtering the molten MoO 2 Cl 2 .
18. The method of claim 16, further comprising the step of: f) venting the vessel again.
19. 17. The method of claim 16, wherein the heating step of step b comprises heating the vessel to a temperature of from 180°C to 200°C.
20. The ultra-high purity MoO of claim 1, having a packing density of 0.7 kg / L to 1.5 kg / L (outside container volume). 2 C 2 Contains a container.
21. 2. The ultra-high purity MoO of claim 1 having less than 300 ppm by volume of gaseous HCl. 2 C 2 The gas phase contains